IS THERE A MARKET FOR BRANDED GULF OF MEXICO OYSTERS?. (16th January 2017) - PETROLIA, DANIEL R.; WALTON, WILLIAM C.; YEHOUENOU, LAURIANE
Abstract: We administered an online choice experiment to a sample of U.S. raw-oyster consumers to identify factors influencing preferences for Gulf of Mexico oysters, determined the extent of preference heterogeneity, and estimated marginal willingness to pay for specific varieties and other key attributes. Results indicate significant preference heterogeneity among select varieties, with non-Gulf respondents estimated to require a price discount on Gulf oyster varieties on the order of 3–6/half dozen. Gulf respondents were found to be less sensitive to oyster variety, and estimated to be willing to pay a price premium only for select Gulf varieties on the order of 0–3/half dozen.